FAKTOR YANG MEMPENGARUHI KEUANGAN DAERAH - Andini Indriani; Hermi Hermi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
This study aims to analyze the influence of government internal control system and internal control on fraud prevention and its implications on the quality of local financial statements. The sample used in this study were is 89 respondents to local government officials Bogor and Depok. The test is done by using multiple linear regression analysis, the data is processed using SPSS. The result of the research shows that the influence of internal control system influences positively to fraud prevention, while internal control has no effect on fraud prevention, while fraud prevention has a positive effect on the quality of financial statements. The Government Internal Control System has a negative effect on the quality of Regional Financial Report and Internal Control has a positive effect on the Quality of Local Financial Report. Internal control system of government indirectly affect the quality of local financial statements through fraud prevention, internal control directly affect the quality of local financial statements through fraud prevention. Fraud prevention has a greater impact on the quality of local financial statements. Internal control system of a business entity is strong, then the possibility of the occurrence of errors and fraud can be minimized It means that the more successful prevention fraud the quality of financial reporting of the region is increasing.